Perovskite Solar Cells: Understanding the Role of Cesium and Rubidium Additives in Perovskite Solar Cells: Trap States, Charge Transport, and Recombination (Adv. Energy Mater. 16/2018). Issue 16 (5th June 2018) - Hu, Yinghong; Hutter, Eline M.; Rieder, Philipp; Grill, Irene; Hanisch, Jonas; Aygüler, Meltem F.; Hufnagel, Alexander G.; Handloser, Matthias; Bein, Thomas; Hartschuh, Achim; Tvingstedt, Kristofer; Dyakonov, Vladimir; et al.
Abstract : In article number1703057, Andreas Baumann, Tom J. Savenije, Michiel L. Petrus, Pablo Docampo and co‐workers demonstrate that the incorporation of Cs + cations into lead halide perovskites reduces the trapping of photogenerated charge carriers in deep trap states. This can be related to an increase of open‐circuit voltage in perovskite solar cells. Cover Image by Christoph Hohmann, Nanosystems Initiative Munich (NIM).